Factors Predicting Sleep Quality Among School-Age Children in Bangkok Metropolis - Thaibandit, Jaruwan; Wongchan, Waraphan; Nontharux, Karuna (Journal of The Royal Thai Army Nurses, 2025)
This research aimed to study the factors predicting sleep quality among school-aged children in Bangkok metropolis. The sample consisted of 418 students in grades 4 to 6 from elementary schools in Bangkok. Participants were selected through multi-stage sampling. The research tools included the following questionnaires: 1) demographic information, 2) emotional problem and peer relationship questionnaire, 3) electronic media usage behaviors, 4) physical activity behavior questionnaire, and 5) sleep quality questionnaire. Data were analyzed by using descriptive statistics, Chi-square, Spearman’s rank correlation coefficient, and logistic regression analysis. The results revealed that the majority of school-aged children (83.25%) had poor overall sleep quality. Emotional problem and peer relationship, electronic media usage behaviors, and physical activity behavior were significantly correlated with sleep quality (r = .12, .32, p < .05 and r = -.24, p < .001, respectively). These factors also predicted sleep quality (ORadj = 3.31, 95%CI = 1.38-7.98; 3.67, 95%CI = 1.99-6.78; and 11.90, 95%CI = 4.70-30.07, respectively) and together explained 31.7% of the variance in sleep quality among school-age children (Nagelkerke R² = .31).